(untitled) (Development Service Industry Management, 2025)
Private Label in domestic retail is a key strategic tool for increasing profitability (or maximizing margin). Inflation and the war have pushed consumers towards rational purchases, and retailers towards intensively increasing the share of Private Label. The goal of the article is to determine the motives that drive consumers to purchase Private Label products, and also to outline the current trends of Private Label in domestic food retail and the prospects for their development. The Private Labels of the five largest food retailers in Ukraine were examined, the names of their main Private Labels were provided, and their own focus and features of the Private Label assortment portfolio were identified, which correspond to their main format and target audience. It is noted that Private Labels have transformed from a simple "cheap alternative" into a full-fledged, competitive, and reliable brand, whose success is based on the synergy of economic advantages, growing trust in retail, and convenience of purchase. Groups of rational motives are presented, which are driven by the economic situation, general instability, as well as growing trust in the quality of retail brands, encouraging consumers to choose retail Private Label products. Based on the identified consumer motive groups for purchasing retail Private Label and the features of the main focus of the most significant players in the domestic market, trends that are currently relevant, as well as those that will have a tendency toward rapid development, were defined. Directions for the development of Private Label in domestic retail are proposed: development and implementation of innovative assortment, enhancement of retail brand reputation, and personalization.